REFORMASI SISTEM PERADILAN DALAM PENANGANAN KASUS PENYEROBOTAN TANAH: EVALUASI KASUS DR. UMMIE WASITOH DI KABUPATEN BANDUNG - deddi fasmadhy (Justicia Journal, 2025)
Land encroachment in Indonesia is a criminal offense that often disrupts legal certainty and land ownership rights. One prominent case is the case involving Dr. Ummie Wasitoh in Bandung Regency, which reflects significant challenges in land law enforcement in Indonesia. Despite the existence of binding legal rulings, the execution of these rulings is often hindered by various obstacles such as intervention from certain parties, limited resources, and weak coordination among law enforcement agencies. This study aims to analyze the judicial system applied in handling land encroachment cases, specifically in the context of the Dr. Ummie Wasitoh case, and to evaluate the factors influencing the effectiveness of law enforcement in such cases. The research method used is a normative juridical approach, analyzing relevant regulations such as the Criminal Code (KUHP), the Agrarian Law, and other related laws. Data is collected through literature study, analysis of court decisions, and interviews with relevant parties, including legal counsels, law enforcement officers, and affected communities. The research findings indicate that despite clear and firm legal rulings, their implementation is often obstructed by structural issues, such as weak coordination among law enforcement officers and a lack of transparency in the execution procedures. The study concludes that to improve the effectiveness of the judicial system in handling land encroachment cases, policy reforms are necessary to support the integration of more robust regulations, transparent execution systems, and improved coordination among agencies. Additionally, the role of the community and public participation is also crucial in ensuring smooth law enforcement